Pharmacokinetics, distribution, metabolism, and excretion of the dual reuptake inhibitor [14C]-nefopam in rats. (1st November 2016) - Yu, Jian; Solon, Eric; Shen, Helen; Modi, Nishit B.; Mittur, Aravind
Abstract: 1. This study examined the pharmacokinetics, distribution, metabolism, and excretion of [ 14 C] nefopam in rats after a single oral administration. Blood, plasma, and excreta were analyzed for total radioactivity, nefopam, and metabolites. Metabolites were profiled and identified. Radioactivity distribution was determined by quantitative whole-body autoradiography. 2. The pharmacokinetic profiles of total radioactivity and nefopam were similar in male and female rats. Radioactivity partitioned approximately equally between plasma and red blood cells. A majority of the radioactivity was excreted in urine within 24 hours and mass balance was achieved within 7 days. 3. Intact nefopam was a minor component in plasma and excreta. Numerous metabolites were identified in plasma and urine generated by multiple pathways including: hydroxylation/oxidation metabolites (M11, M22a and M22b, M16, M20), some of which were further glucuronidated (M6a to M6c, M7a to M7c, M8a and M8b, M3a to M3d); N-demethylation of nefopam to metabolite M21, which additionally undergoes single or multiple hydroxylations or sulfation (M9, M14, M23), with some of the hydroxylated metabolites further glucuronidated (M2a to M2d). 4. Total radioactivity rapidly distributed with highest concentrations found in the urinary bladder, stomach, liver, kidney medulla, small intestine, uveal tract, and kidney cortex without significant accumulation or persistence. Radioactivity reversibly associated with melanin-containing tissues.